Broken republic : three essays - Roy, Arundhati (New Delhi : Hamish Hamilton, 2011)
On Naxalite movement and Indian state's counter insurgency methods and other policies.
Includes bibliographical references (p. 215-220).
Keywords: Naxalite movement; Counterinsurgency -- India; India -- Politics and government -- 21st century